The Influence of Non-Clinical Patient Factors on Clinical Decision Making: Uncovering the Impact on Mental Health - Burns, Lauren; Sergio da Silva, Ana; John, Ann (International Journal of Population Data Science, 2019)
Background Understanding how non-clinical patient factors (NCpF) such as gender, educational level and socioeconomic status impact clinical decisions regarding one’s mental health is important for appropriate and equitable care. Main Aim This research aims to i) investigate the feasibility of using administrative health data to investigate clinical decision making in mental health; ii) understand the impact of NCpF on mental health-related diagnosis, treatment, and referral decisions. Methods/Approach Three waves of the Welsh Health Survey, containing a five-item Mental Health Inventory (Short- Form SF36), and NCpF information were used to create our interest cohort. The records with a low SF36, a ‘gold standard’ identifier of common mental health conditions, were then linked to the healthcare records datasets (Primary Care GP Dataset, Patient Episode Database for Wales, Emergency Department Dataset, Outpatient Referral Dataset, Annual District Death Extract) securely stored on the Secure Anonymised Information Linkage Databank. Results We will present the methodological challenges and benefits of using administrative data the study of decision making in mental health. The differences in NCpF between those with a low SF36 and a mental health diagnosis, symptoms and treatment as well as those with a similar SF36 score but no diagnosis, symptoms or treatment recorded will be presented and discussed. Conclusion Administrative data can provide a unique opportunity to investigate issues related with clinical decision-making in mental health and improve health equity. Having a better understanding of the influence of NCpF on mental health decisions is necessary to prevent inequity in mental health care.